The Psychological Framework of the Shahada: An Integrative Model of Faith and Mental Health - Ruddin, Fajar; Ilahi, Rahmad; Taufik (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The shahada, the foundational declaration of faith in Islam, exerts profound influence on the psychological dimensions of a Muslim's life. This article seeks to examine the psychological facets of the shahada through a comprehensive literature review. The research identifies three primary dimensions: cognitive beliefs, emotional commitment, and behavioral expression. Cognitive beliefs derived from the shahada provide a mental framework that shapes perceptions and decisions, enabling individuals to interpret life experiences within the Islamic worldview. Emotional commitment to the shahada fosters emotional stability and well-being, thereby reinforcing spiritual bonds with Allah and His Messenger. Meanwhile, behavioral expression reflects the manifestation of the shahada in everyday actions, strengthening self-identity and enhancing social cohesion within the Muslim community. The integration of these three dimensions demonstrates that the shahada is not merely a declaration of faith but a profound psychological foundation that supports mental health and well-being. This article underscores the critical importance of a deep understanding of the shahada within the context of Islamic psychology and its broader implications for mental health practice and spiritual life.